2015
DOI: 10.1007/s41063-015-0013-9
|View full text |Cite
|
Sign up to set email alerts
|

The role of Arctic Ocean freshwater during the past 200 ky

Abstract: As part of the hydrologic cycle, the freshwater system plays a pivotal role for the Arctic Ocean. It maintains the strong stratification in the upper waters and fosters the formation of sea ice on the circum-Arctic shelves from where the ice is being exported toward Fram Strait and into the Nordic Seas. Recent projections of climate change under the greenhouse effect predict severe changes for the hydrologic cycle in the Arctic. This manuscript reviews the current knowledge of past changes in freshwater fluxes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 97 publications
0
4
0
Order By: Relevance
“…Higher than modern sea surface temperatures (SSTs) during the last interglacial maximum (MIS 5.5), about 125 thousand years (125 ka) ago, were accompanied by reduced ice volume and corresponding sea level rise (e.g., Kopp et al, 2009;Rohling et al, 2014). Freshening of polar surface waters has been observed along with past and modern climate warming and sea ice retreat (e.g., Haas et al, 2008;Spielhagen and Bauch, 2015;Haumann et al, 2016). Climate model projections indicate an asymmetric warming between the Arctic and Southern Ocean, with an early response in the Arctic and a delayed response in the Southern Ocean: Northern polar regions are projected by modeling studies to be subjected to warming mostly through persistent Atlantic Meridional Overturning, also referred to as polar amplification (e.g., Manabe and Stouffer, 1980;Manabe et al, 1991;Meehl et al, 2007).…”
Section: Modern Environment and Climate Changementioning
confidence: 99%
“…Higher than modern sea surface temperatures (SSTs) during the last interglacial maximum (MIS 5.5), about 125 thousand years (125 ka) ago, were accompanied by reduced ice volume and corresponding sea level rise (e.g., Kopp et al, 2009;Rohling et al, 2014). Freshening of polar surface waters has been observed along with past and modern climate warming and sea ice retreat (e.g., Haas et al, 2008;Spielhagen and Bauch, 2015;Haumann et al, 2016). Climate model projections indicate an asymmetric warming between the Arctic and Southern Ocean, with an early response in the Arctic and a delayed response in the Southern Ocean: Northern polar regions are projected by modeling studies to be subjected to warming mostly through persistent Atlantic Meridional Overturning, also referred to as polar amplification (e.g., Manabe and Stouffer, 1980;Manabe et al, 1991;Meehl et al, 2007).…”
Section: Modern Environment and Climate Changementioning
confidence: 99%
“…While the Arctic's FWV decreased in the initial years to 71,220 km 3 in 1985, it has subsequently sustained an increase, reaching a maximum of 90,450 km 3 in 2018. On average, the Arctic Ocean's FWV has been reported to be roughly 84,000 km 3 when using a reference salinity of 34.8 psu (Serreze et al., 2006; Spielhagen & Bauch, 2015). Here, ORAS5 shows a comparable FWV of 80,763 km 3 (Table 1), with the Russian Shelf contributing ∼16% and the BG ∼23%.…”
Section: Resultsmentioning
confidence: 99%
“…Ahmed et al (2020) reported that the annual discharge over the years 1980-2009 from the Ob, Lena, and Yenisei Rivers increased by 10.3, 40.6, and 23.7 km 3 per decade respectively. Arctic shelves also tend to favor polynyas where ice grows and an excess of saline water is left behind (Spielhagen & Bauch, 2015). Both factors contribute greatly to seasonal and interannual variability.…”
mentioning
confidence: 99%
“…Inflow of Pacific Waters through Bering Strait and export of ice and low‐saline waters through Fram Strait are indicated. Gray arrows mark the average surface water circulation within the Beaufort Gyre and the Transpolar Drift and red arrows the places of sinking water masses (Spielhagen & Bauch, , supplemented; based on data from EWG, ).…”
Section: The Arctic Ocean: Characteristics and Significance For The Cmentioning
confidence: 99%